The Effect of Leverage, Profitability, Company Size, and Institutional Ownership on Profit Management Using Modified Jones, A Meta-Analysis Study - Anatapindika Fong; Patrick Prajnananda Ruci; Katherine Nastasya Herman; Carmel Meiden; Prima Apriwenni (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2022)
Apart from being a form of management accountability for the use of entrusted resources, the profit and loss condition of a company is also often used by the company's stakeholders widely because it has predictive value. This makes the management try to do earnings management so that the company's performance looks better by external parties. Many studies related to the effect of leverage, profitability, company size, and/or institutional ownership on earnings management actions have been carried out and have different significance results. This study aims to expand the theory and remove inconsistencies in the research results by using meta-analysis techniques. Meta-analysis itself is a way that can integrate the results of existing studies and reveal patterns of relative invariance and causes of differences in results. The data taken in this study are secondary data taken through various sources in the form of journals, research results, and literature studies that discuss the factors that influence earnings management actions. This study uses the Modified Jones model in detecting the presence of earnings management in a company. The data collection technique used the observation method using data from previous studies. The sample data used for this study were 29 studies. The results of the meta-analysis show that leverage, profitability, firm size and institutional ownership have a significant effect on earnings management actions.